1999
DOI: 10.1073/pnas.96.16.9322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the high density lipoprotein receptor SR-BI on reproductive and cardiovascular pathophysiology

Abstract: The high density lipoprotein (HDL) receptor SR-BI (scavenger receptor class B type I) mediates the selective uptake of plasma HDL cholesterol by the liver and steroidogenic tissues. As a consequence, SR-BI can inf luence plasma HDL cholesterol levels, HDL structure, biliary cholesterol concentrations, and the uptake, storage, and utilization of cholesterol by steroid hormone-producing cells. Here we used homozygous null SR-BI knockout mice to show that SR-BI is required for maintaining normal biliary cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
494
2
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(533 citation statements)
references
References 69 publications
23
494
2
7
Order By: Relevance
“…Evidence is accumulating that cholesterol must be considered as an essential agent in embryonic development. Histochemical analysis of ovaries from superovulated females showed reduced oil red O staining of lipids in the ovarian copora lutea of SR-BI knock out relative to those of wild-type animals suggesting reduced CE storage as a source for steroid hormone production [61]. Also plasma progesterone levels between pseudopregnant controls and knock out females 6 days after mating were slightly although not significantly impaired.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Evidence is accumulating that cholesterol must be considered as an essential agent in embryonic development. Histochemical analysis of ovaries from superovulated females showed reduced oil red O staining of lipids in the ovarian copora lutea of SR-BI knock out relative to those of wild-type animals suggesting reduced CE storage as a source for steroid hormone production [61]. Also plasma progesterone levels between pseudopregnant controls and knock out females 6 days after mating were slightly although not significantly impaired.…”
Section: Discussionmentioning
confidence: 89%
“…Also plasma progesterone levels between pseudopregnant controls and knock out females 6 days after mating were slightly although not significantly impaired. Finally, the majority of embryos from SR-BI knock out females at harvesting showed abnormal, nonrefractile morphology of oocytes and embryos [61] similar to wild-type females that had been treated with cholesterol-binding drugs that can perturb membrane structure. Female mice with a targeted null mutation of the SR-BI gene are infertile [61], a fact underscoring the importance of the SR-BI pathway during embryonic development.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may also contribute to the decrease in the plasma corticosterone level in SR-BI-deficient mice. Importantly, Trigatti et al (27) have shown that female SR-BIdeficient mice are infertile, probably because of a similarly impaired steroidogenesis in the ovaries. Given the fact that SR-BI-deficient mice have very high circulating levels of ACTH, a potent activator of adrenal cortex glucocorticoid production (28), and a concomitant increase in adrenal weight under fasting conditions, it is suggested that SR-BI-deficient mice are unable to respond adequately to physiological stress impulses, as they suffer from adrenal glucocorticoid insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although the selective deletion of ABCA1 in macrophages (Brunham et al, 2009) and the overexpression of ABCG1 (Burgess et al, 2008) did not significantly modulate the development of atherosclerotic plaques, simultaneous deficiency in both ABCA1 and ABCG1 promoted atherosclerosis in mice (Yvan-Charvet et al, 2007). In addition to ABCA1 and ABCG1, SR-BI, another type B scavenger receptor, protects against atherosclerosis when expressed in macrophages by stimulating cholesterol efflux, whereas genetically suppressing SR-BI activity in ApoE-deficient mice dramatically accelerates the onset of atherosclerosis (Trigatti et al, 1999). The SR-BI-mediated reverse cholesterol transport process demonstrated in macrophages was confirmed in vivo using ABCA1/SR-BI double knockout mice (Zhao et al, 2011).…”
Section: Cholesterol Effluxmentioning
confidence: 99%